Pneumonia-associated death in patients with dementia: A systematic review and meta-analysis - Manabe, Toshie; Fujikura, Yuji; Mizukami, Katsuyoshi; Akatsu, Hiroyasu; Kudo, Koichiro (PloS one, 2019)
Pneumonia is a serious disease associated with mortality among patients with dementia. However, the reported frequency of pneumonia as a cause of death in patients with dementia varies, the reason for which has not been fully elucidated. We conducted a systematic search in PubMed and the Cochrane Database of Systematic Reviews (inception to December 2016). Two authors independently determined the suitability of studies and potential bias and extracted the data. The primary outcome was frequency of pneumonia-associated death in patients with dementia. Stratified subgroup analysis was conducted among studies grouped according to type of mortality cause (immediate or underlying), information source of mortality cause (autopsy or death certificate), and study setting (clinic, hospital, or nursing home). We included 7 studies reporting the cause of death among patients with dementia and 12 studies comparing the cause of death among patients with and without dementia. The frequency of pneumonia-associated death among 19 eligible studies was 29.69% (95% confidence interval [CI], 25.86-33.53). Those frequencies differed according to whether the source for information about cause of death was an autopsy confirmation (49.98%; 95% CI, 43.75-56.71) or death certificate (19.65%; 95% CI, 15.48-23.83) and according to whether the type of mortality cause was an indirect cause of death (13.96%; 95% CI, 9.42-18.51) or direct cause of death (44.45%; 95% CI, 29.81-50.10). The risk of pneumonia-associated death in patients with dementia was twice as high as among those without dementia (odds ratio, 2.15; 95% CI, 1.63-2.83; p < 0.001). The various frequencies of pneumonia-associated death in patients with dementia were associated with the information source, type of mortality cause, and study setting. Patients with dementia in the terminal stages urgently require careful clinical management of pneumonia, to maximize patient life expectancy and quality.